Regional economic organization in Africa - Ndongko, Wilfred Awung (Friedrich-Ebert-Stiftung [u.a.], 1987)
The study will attempt to critically analyze the real and potential economic problems of these regional groupings in the light of the provisions, of the various treaties and agreements, which deal with the objectives of trade liberalization, financial, fiscal and monetary harmonization, industrial cooperation and harmonization, and the free mobility of persons and citizens
Mit statist. Übersichten
Keywords: Bibliographie enthalten; Graue Literatur; Forschungsbericht; Wirtschaftsintegration; Afrika; Wirtschaftliche Integration; Völkerrechtlicher Vertrag; Verbindlichkeit; Völkerrecht; Außenhandel